Using method of Holt for analys of data sets - Васильєв, О. С.; Лилка, О. С. (Problems of Informatization and Management, 2010)
Questions of representation of discrete time data and analysis by the method of Holt. Results determined using the method derived coefficients by test data sets and the estimation performance prediction. Created settlement letter seredovyschi Microsoft Excel for research and this method of selection coefficients and study the effectiveness of the method